Analysis Of Hate Speech In The Comments Section Of The Ahmadsahroni88 Account - Oktavianus Dagung; Ni Made Diana Erfiani; Yohanes Octovianus Lesu Awololon (Arus Jurnal Sosial dan Humaniora, 2026)
This study aimed to analyze the forms, characteristics, and linguistic realization strategies of hate speech found in the comments section of Ahmad Sahroni's Instagram account (@ahmadsahroni88). In digital communication, the social media accounts of public figures often turn into complex public discourse arenas that facilitate aggressive interactions. This study employed a descriptive qualitative approach with content analysis as the primary method. Data consisting of user comments indicating hate speech were collected from several highly interactive posts employing a purposive sampling technique. The gathered data were systematically classified and analyzed based on Brown and Levinson's politeness theory, focusing on the concept of Face Threatening Acts (FTAs). The results revealed that hate speech mainly occurred in the forms of insults, provocations, and threats, while several comments reflected positive politeness strategies through constructive criticism and advice. Insults delivered through a bald on-record strategy were the most prevalent form, directly attacking the target's positive face without any mitigation. Provocations were frequently realized via off-record strategies such as sarcasm and irony, allowing speakers to maintain plausible deniability. Threats targeting the interlocutor's negative face were also identified. This study concludes that online hate speech is a multidimensional social practice heavily influenced by political polarization and digital anonymity.